Communities of Musical Practice (Ailbhe Kenny: Routledge, 2016) - Garry, Fran (Irish Journal of Arts Management and Cultural Policy, 2017)
A review of Communities of Musical Practice by Ailbhe Kenny, which explores ‘situated’ collaborative music-making practices on the ground in Ireland. Communities of Musical Practice by Ailbhe Kenny provides an in-depth and invaluable insight into ‘situated’ collaborative music-making practices on the ground in Ireland. The central research question – ‘how are ‘communities of musical practice’ developed and sustained in practice?’ (p. 1) – is addressed through qualitative case study research in Ireland’s mid-west region and situated within a broader sociocultural theoretical and contextual framework concerning music education. The author analyses and interprets complex practices using a Community of Musical Practice (CoMP) framework, adapted from Lave and Wenger’s Community of Practice (CoP) model, in addition to drawing on the sociocultural theoretical perspectives of Bourdieu, Becker and de Certeau.